2012
DOI: 10.1016/j.rinim.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The long-term immunogenicity of an inactivated split-virion 2009 pandemic influenza A H1N1 vaccine: Randomized, observer-masked, single-center clinical study

Abstract: The aim of this study is to investigate the long-term immunogenicity of inactivated split-virion 2009 pandemic influenza A H1N1 vaccine after a single immunization. We recruited 480 adults, aged 18-60 years, for a placebo-controlled, observer-masked, single-center clinical study. We randomly assigned subjects into four groups: 15 μg, 30 μg and 45 μg of hemagglutinin (HA) dosage groups, and a placebo control group. Finally, 259 subjects completed the entire study. The rates of seroconversion and seroprotection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…We found that in Part B subjects (one VLP dose), after 21 months of VLP vaccination, the GMT values were higher in VLP recipients than in the placebo group. Our results are in agreement with other studies, where it has been reported that antibodies to the A(H1N1)pdm09 virus can still be detected in adults up to at least 12 months after vaccination with various inactivated, split-virion H1N1 pandemic influenza vaccines [ 39 44 , 48 , 49 ]. Consistent with our findings, Landry et al, recently showed that a non-adjuvanted plant-made H1N1 pandemic influenza virus VLP vaccine induced detectable antibody levels up to 6 months after vaccination [ 12 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that in Part B subjects (one VLP dose), after 21 months of VLP vaccination, the GMT values were higher in VLP recipients than in the placebo group. Our results are in agreement with other studies, where it has been reported that antibodies to the A(H1N1)pdm09 virus can still be detected in adults up to at least 12 months after vaccination with various inactivated, split-virion H1N1 pandemic influenza vaccines [ 39 44 , 48 , 49 ]. Consistent with our findings, Landry et al, recently showed that a non-adjuvanted plant-made H1N1 pandemic influenza virus VLP vaccine induced detectable antibody levels up to 6 months after vaccination [ 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, after 25 months, we found a similar tendency in both the seroprevalent and seroprotective antibody levels in VLP vaccinated subjects compared with the placebo treated subjects. The SPR values that were found in the VLP recipients were lower (22.8–29.8%), compared with those reported in other egg-produced, non-adjuvanted, pandemic H1N1 vaccines, which, in adults, reached values from 46% up to 68% after 12 months [ 39 , 42 , 49 ]. In the case of adjuvanted vaccines (with MF59 or AS03), the SPR values reported elsewhere ranged from 35% [ 43 ] up to above 70% [ 40 , 44 , 48 ].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The inactivated split-virion vaccine against the H1N1 (2009) virus was developed by the Shanghai Institute of Biological Products, and the seed virus was prepared from the reassortant vaccine virus A/California/7/2009 NYMC X-179A, as described in our previous study (13).…”
Section: Methodsmentioning
confidence: 99%
“…However, the level of antibody in serum decreased postimmunization. Vaccination with a single 15-g dose of HA split vaccine can induce a protective immune response persisting for at least 6 months in adults only (13). In view of this, we hope to extend the effectiveness of the vaccine by the means of an adjuvant.…”
mentioning
confidence: 99%